Arabidopsis phospholipase Dζ2 facilitates vacuolar acidification and autophagy under phosphorus starvation by interacting with VATD - Bin Guan; Ke-Xuan Xie; Xin-Qiao Du; Yu-Xuan Bai; Peng-Chao Hao; Wen-Hui Lin; Jiří Friml; Hong-Wei Xue (Cell Reports)
Summary: Vacuolar acidification is crucial for the homeostasis of intracellular pH and the recycling of proteins and nutrients in cells, thereby playing important roles in various physiological processes related to vacuolar function. The key factors regulating vacuolar acidification and underlying mechanisms remain unclear. Here, we report that Arabidopsis phospholipase Dζ2 (PLDζ2) promotes the acidification of the vacuolar lumen to stimulate autophagic degradation under phosphorus deficiency. The pldζ2 mutant massively accumulates autophagic structures while exhibiting premature leaf senescence under nutrient starvation. Impaired autophagic flux, lytic vacuole morphology, and lytic degradation in pldζ2 indicate that PLDζ2 regulates autophagy by affecting the vacuolar function. PLDζ2 locates in both tonoplast and cytoplasm. Genetic, structural, and biochemical studies demonstrate that PLDζ2 directly interacts with vacuolar-type ATPase (V-ATPase) subunit D (VATD) to promote vacuolar acidification and autophagy under phosphorus starvation. These findings reveal the importance of V-ATPase and vacuolar pH in autophagic activity and provide clues in elucidating the regulatory mechanism of vacuolar acidification.